2022
DOI: 10.5114/biolsport.2022.102867
|View full text |Cite
|
Sign up to set email alerts
|

How does curve sprint evolve across different age-categories in soccer players?

Abstract: Research has shown that soccer players regularly execute curved sprints during matches. The purpose of this study was to determine the age-related effects on curve sprint (CS) performance to both sides, asymmetry, and association with linear sprint (LS). Eighty-four soccer players (aged 16.1 ± 1.6 categorized in U15, U17, and U20) were recruited, who performed CS and LS tests. One-way analysis of variance (ANOVA) and effect size (ES) were used to compare CS performance between age categories, and relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Therefore, these respective capacities are considered key elements during the organization and planning of strength and conditioning practices in soccer (25,47). Importantly, throughout soccer matches, sprint efforts occur over different trajectories, intensities, and distances, involving curved paths, rapid accelerations and decelerations, and aggressive directional changes (4,5,10). The concomitant development of these multiple sprint-related capabilities is extremely challenging for coaches, who frequently have to deal with congested training and match schedules, which, combined with high volumes of aerobic stimuli across the competitive season, tend to compromise the adequate prescription and reduce the effectiveness of sprint-specific training in soccer (25,36).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these respective capacities are considered key elements during the organization and planning of strength and conditioning practices in soccer (25,47). Importantly, throughout soccer matches, sprint efforts occur over different trajectories, intensities, and distances, involving curved paths, rapid accelerations and decelerations, and aggressive directional changes (4,5,10). The concomitant development of these multiple sprint-related capabilities is extremely challenging for coaches, who frequently have to deal with congested training and match schedules, which, combined with high volumes of aerobic stimuli across the competitive season, tend to compromise the adequate prescription and reduce the effectiveness of sprint-specific training in soccer (25,36).…”
Section: Discussionmentioning
confidence: 99%
“…In a more applied perspective, contextualized HIA implies the individualization of these activities, however this concept seems not yet to be widely implemented. Although some HIA are interrelated during early stages of the soccer career, skill differentiation will inevitably occur as a consequence of the specialization process [67]. According to recent findings, when athletes achieve high levels of physical maturation and experience, skills that seemed similar (e. g. COD and agility) are usually manifested as independent skills [67,68].…”
Section: Training Backgroundmentioning
confidence: 99%
“…Although some HIA are interrelated during early stages of the soccer career, skill differentiation will inevitably occur as a consequence of the specialization process [67]. According to recent findings, when athletes achieve high levels of physical maturation and experience, skills that seemed similar (e. g. COD and agility) are usually manifested as independent skills [67,68]. Furthermore, movement coordination pattern is exclusively unique to individuals at the end of the specialization process, and even among players with similar playing positions (and similar game tasks), the coordination pattern could be different among individuals [69].…”
Section: Training Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…12 By contrast, other studies found higher correlations of r = 0.67-0.76, 15 r = 0.74-0.82, 14 and even r = 0.93-0.95, 16 which might be attributed to other age groups and performance levels of players being investigated. 17 However, only the abovementioned CS test using a radius of 9.15 m was applied in all of these studies. Conversely, as neuromuscular and biomechanical differences are evident between LS and CS due to the emerging centrifugal forces during the latter, 18 changing the radius during CS might also alter such neuromuscular and biomechanical characteristics, and therefore, performance in the respective tasks.…”
Section: Introductionmentioning
confidence: 99%